“Estrategia didáctica con herramientas digitales de aprendizaje para el fortalecimiento de Matemática en Séptimo Año” - Balarezo Morales, Marcela (2022)
The work that is presented sought to deepen the educational environment of mathematics teaching in the Seventh Year of Basic General Education of the Educational Unit "19 de Septiembre" having detected that these students show demotivation in their learning caused by a monotonous teaching which This makes the subject difficult to understand. The general objective was to determine a digital tool to strengthen the learning of the subject indicated in the students under study. Methodologically, the study had a qualitative approach and the descriptive, explanatory, bibliographical-documentary and field methods were applied, with the main result being Canva's proposal as a digital learning tool, which is currently considered an excellent didactic strategy to work with. virtual sources of information that replace the traditional one-way media, since it requires the student to work autonomously, collaboratively, critically, creatively, individually and in groups, as well as research in an exchange of resources and creation of new knowledge.